Accidents by scorpio Tityus sp. (scorpiones: Buthidae) in children: two orbit report (Research, Society and Development, 2021)
Objective: to describe two cases of child accidents with scorpion of the genus Tityus serrulatus with death outcome and the duration of antiscorpionic serotherapy.Methodology:descriptive and documentary study, in the multiple case study modality, carried out from two cases of infantile scorpionism notified to an information and toxicological assistance center in Paraná, in 2017. Data were collected from epidemiological records of Accidents by Venomous Animals - Scorpion, Home Visit records and children’s medical charts.Results: early severity of the cases and the need of early serotherapy, in addition to the need of intensive care unit and health teams for high complexity care were found, setting scorpion accidents as real health emergencies.Conclusion: as lessons from the cases, positive aspects were found in care, such as the early access to the health unit and the identification of signs and symptoms, but the time between the accident and antiscorpionic serotherapy was longer than recommended, determining the outcome of the cases.